Gecko-Inspired Adhesive Mechanisms and Adhesives for Robots—A Review - Soumya Sikdar; Md Hafizur Rahman; Arpith Siddaiah; Pradeep L. Menezes (Robotics, 2022)
Small living organisms such as lizards possess naturally built functional surface textures that enable them to walk or climb on versatile surface topographies. Bio-mimicking the surface characteristics of these geckos has enormous potential to improve the accessibility of modern robotics. Therefore, gecko-inspired adhesives have significant industrial applications, including robotic endoscopy, bio-medical cleaning, medical bandage tapes, rock climbing adhesives, tissue adhesives, etc. As a result, synthetic adhesives have been developed by researchers, in addition to dry fibrillary adhesives, elastomeric adhesives, electrostatic adhesives, and thermoplastic adhesives. All these adhesives represent significant contributions towards robotic grippers and gloves, depending on the nature of the application. However, these adhesives often exhibit limitations in the form of fouling, wear, and tear, which restrict their functionalities and load-carrying capabilities in the natural environment. Therefore, it is essential to summarize the state of the art attributes of contemporary studies to extend the ongoing work in this field. This review summarizes different adhesion mechanisms involving gecko-inspired adhesives and attempts to explain the parameters and limitations which have impacts on adhesion. Additionally, different novel adhesive fabrication techniques such as replica molding, 3D direct laser writing, dip transfer processing, fused deposition modeling, and digital light processing are encapsulated.